Study approach and field work procedures of the MentDis_ICF65+ project on the prevalence of mental disorders in the older adult European population - Volkert, Jana (BMC psychiatry, 2017)
This study describes the study approach and field procedures of the MentDis_ICF65+ study, which aims to assess the prevalence of mental disorders in older adults.